(untitled) (Bangladesh Veterinarian, 2010)
The status of ulcer diseases in cultured fish in 14 upazilas (sub-districts) of Mymensingh and surrounding six districts were investigated during the winter in 2001-2002 and 2002-2003. Fish were visibly affected by ulcer diseases including epizootic ulcerative syndrome (EUS). Prevalence of disease varied in different districts, months and fish species in the two years. The highest prevalence of disease was in Jamalpur district where 90% fish ponds in Melandah upazila were affected during 2001-2002, whereas 80% affected ponds were observed in sadar upazila of Mymensingh district during 2002-2003. The highest prevalence was in January and the lowest in October. The prevalence of ulcer diseases in different fish species varied significantly (p<0.01). Among the 10 affected species, six were histopathologically EUS-positive and four EUS-negatives. Cirrhinus cirrhosus and Barbodes gonionotus were highly affected by ulcer diseases including EUS. DOI: 10.3329/bvet.v25i1.4617 Bangl. vet. 2008. Vol. 25, No. 1, 40-49